Chinese Outward Foreign Direct Investment and Innovation in Host Countries: Evidence from Countries Along the Belt and Road. (May 2023) - Sun, Yanyan; Fan, Sha
Foreign direct investment (FDI) can benefit innovation activity in host countries through spillover channels, such as reverse engineering, demonstration effects, and supplier–customer relationships. Using data from 26 countries along the Belt and Road route (BRCs) and 32 non-BRCs, we identified positive causal effects of the Chinese outward FDI on the innovation capacities in technology-intensive industries of both BRCs and non-BRCs. However, this effect varies depending on the host countries' economic development levels. The impact of Chinese OFDI on the general innovation performance in host countries is absent. Meanwhile, the implementation of the BRI has on the whole, a negative impact on BRCs' innovation performance.